Natureza capitalista versus natureza orgânica: o advento da ALCOA e a mobilização e organização das comunidades de Juruti no baixo-amazonas paraense - SILVA, Lindomar de Jesus de Sousa (Universidade Federal do Pará, 2014)
The thesis aims to show the reading and analysis of the processes that led to unprecedented achievements involving communities in Juruti, low Amazon region located in the state of Pará Juruti was the scene of conflict, negotiations, agreements and achievements with the large enterprise mineral extraction developed by ALCOA. These achievements are the result of external and internal factors. External marked by a favorable set related to the leftist government in federal, state and municipal level, a legal institutional framework that recognizes the collective and territorial rights, emergence of environmental issues and the presence of the Catholic Church, through the pastoral work of the Franciscan Sisters Maristella, guided by liberation theology and pedagogy of the oppressed. Internally prevailed traditional character, community life and collective practices as puxirum, enabled the establishment of an organized and capable of triggering processes of mobilization and resistance with minimal fragmentation and cooptation territory. With support from various theoretical contributions of sociology, anthropology and others who facilitated our reading of the living process in the territory of Juruti, as well as the approaches of post - development. The methodology of the research is exploratory, descriptive and explanatory nature combined with field techniques such as collecting information and interviews with key personnel, company documents, communities, the Catholic Church and others. This procedure aimed to understand the speeches made by the present authors in Juruti. We identified the close relationship of the Church with movements and groups that have embraced the fight in the Juruti region along ALCOA, through the Congregation of the Franciscan Sisters of Maristella, by virtue of its history insertion site, and your choice in defense of traditionalism communities. Also realize an open government favorable to dialogue, there is a favorable political situation; the concern of global society with the environment; the existence of a legal framework to the recognition of institutionalized rights; such as territorial rights. This approach led to the conclusion that given the multiple actions of large projects is necessary to articulate opportunities and potentials in order to seek the ways of overcoming the invisibility given to communities by the state and big business enterprises. Organizational aspects in Juruti well as its articulation led to overcoming the mechanisms of domination, invisibility and standardization of traditional communities in the Amazon.